Pelatihan Pembuatan Pupuk Organik Cair dari Kotoran Sapi sebagai Upaya Pengurangan Limbah di Desa Petiyintunggal, Kecamatan Dukun, Kabupaten Gresik - Eka Kusumawati, Dian; Istiqomah, Istiqomah; Nur Mayang Sari, Devi; Rifqi, Ibrahim; Dwi Oktaviani, Wella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Petiyintunggal Village, located on the western border of Gresik Regency, is predominantly inhabited by farmers and livestock breeders. Cattle raising is a common side activity among the residents. The livestock farming in Petiyintunggal Village is managed traditionally, focusing primarily on the sale of fattened livestock for daily needs, without addressing the environmental impact of accumulated cow dung. To address these issues, the UNISDA 2024 Thematic Real Work Lecture team conducted counseling and training on processing cow dung into beneficial products, specifically liquid organic fertilizer. This training was held in Petiyintunggal Village, Dukun District, Gresik Regency, coordinated with local farmer groups and youth organizations (Karang Taruna). The primary objective was to enhance the community's capacity to produce liquid organic fertilizer as an alternative to chemical fertilizers, utilizing cow dung waste for sustainable farming practices. The training outcomes demonstrated a significant increase in participants' knowledge and skills, approximately 80%, in processing cow dung into liquid organic fertilizer, along with positive feedback and high enthusiasm from the participants.